Overview of the bee genus Trachusa Panzer, 1804 (Hymenoptera: Apoidea: Megachilidae: Anthidiini) from China with description of three new species - Niu, Ze-Qing; Ascher, John S.; Orr, Michael C.; Griswold, Terry; Zhu, Chao-Dong (Zootaxa, 2019)
The Chinese bees of the genus Trachusa Panzer, 1804 are reviewed. Nine species are confirmed to occur in China. Three new species are described and illustrated: Trachusa (Paraanthidium) pingdaensis Niu, sp. nov., T. (P.) staabi Niu, sp. nov. and T. (P.) wuae Niu, sp. nov. The distribution of each species is given. An illustrated key to the Chinese species is provided.